A conical array aerogel and its preparation method and application in steam cracking hydrogen production
By using conical array aerogel materials, combined with electrospinning and annealing processes, a photocatalytic module and photothermal module with high photocatalytic activity are constructed, which solves the problems of catalyst shedding and insufficient seawater adaptability in the existing photocatalytic water cracking hydrogen production system, and achieves a high-efficiency and low-energy-consuming hydrogen production effect of water cracking.
Patent Information
- Application Number
- CN202310070506.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-07
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-02-07
AI Technical Summary
The existing photocatalytic water cracking hydrogen production system faces the problems of catalyst shedding, dissolution or photocorrosion, and it is difficult to adapt to catalytic reactions in seawater or sewage, resulting in insufficient hydrogen production efficiency and catalyst life.
Using a conical array aerogel material, which obtains highly photocatalytic active titanium dioxide nanofibers through electrospinning and annealing processes and combines with hydrophilic polymers to construct photothermal modules with Wenzel-type ultrawetted surfaces and photocatalytic modules with high catalytic activity, and achieves highly integrated reaction devices through a special three-dimensional conical array design.
It realizes high-efficiency, low-energy-consuming water vapor generation and gas-solid two-phase photocatalytic hydrogen production, improves catalytic hydrogen production efficiency, extends the service life of the catalyst, and adapts to catalytic reactions in seawater or sewage.
Smart Images

Figure CN116272698B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an aerogel material, in particular to a cone array aerogel and a preparation method thereof, and also to an application of the cone array aerogel in hydrogen production by water vapor cracking, belonging to the technical field of photocatalysis. Background Art
[0002] Photocatalytic water splitting to produce hydrogen is one of the most important responses to the global energy crisis. Photocatalytic water splitting has potential scalability and technical feasibility, especially it can be performed without external bias, which greatly reduces the cost of producing high-purity hydrogen.
[0003] However, there are some key challenges in the traditional photocatalytic water splitting hydrogen production system based on the liquid-solid-gas three-phase interface. For example, in the flat-plate photocatalytic reaction device that has been gradually developed in recent years and has the prospect of industrial application, the flowing viscous water entering the reactor can continuously elute the photocatalyst powder itself or dissolved ions, thereby causing the photocatalyst to fall off, dissolve or photocorrode, which hinders the construction of the flow catalytic system and the industrialization of photocatalytic hydrogen production. In addition, most photocatalytic water splitting systems are carried out in scarce pure water, which greatly limits their practical application. Seawater is the most easily available natural water source, but it is rarely used for photocatalytic hydrogen production. This is because the salinity of seawater is high, and the salt dissolved in seawater consumes photogenerated carriers, resulting in undesirable side reactions on the catalyst surface. Therefore, in recent years, a more advanced concept has gradually developed, namely photocatalytic water vapor splitting hydrogen production. The system converts liquid water into gaseous water through a pre-placed water vapor generator and transports it to the photocatalytic module for gas-solid two-phase photocatalytic hydrogen production reaction. Theoretically, the gas-solid two-phase reaction system can avoid direct corrosion of the catalyst and provide high-purity substrates for the photocatalytic reaction. In addition, the gas-solid two-phase reaction interface is conducive to the desorption of reaction products, increasing the efficiency of photocatalytic hydrogen production.
[0004] The core technical problem of the water vapor cracking system should be to obtain high-purity water vapor in a low-energy way and maintain a high humidity environment throughout the system. For example, the Domen team of the University of Tokyo in Japan reported a photocatalytic water vapor cracking system (Nat. Commun., 2022, 13, 5698). They used nitrogen as a carrier gas, obtained water vapor by bubbling in a liquid environment, and used pipeline transportation to transfer the water vapor to the photocatalytic module for photocatalytic hydrogen production. This design achieved relatively good photocatalytic hydrogen production performance in seawater and extended the service life of the photocatalyst. However, the complex reaction system and inefficient steam generation capacity greatly increase the cost, manufacturing difficulty and operation and maintenance costs of the system. Wei Bingqing's team at the University of Delaware in the United States reported a photothermal interface-loaded photocatalyst reaction device that can simultaneously produce water vapor and high-purity hydrogen (Nat. Commun., 2021, 12, 1343). It is worth noting that the photothermal effect synergistically improves the catalytic hydrogen production performance of the photocatalyst. However, this device does not construct an ideal gas-solid reaction interface, and the liquid environment and the photocatalyst are not effectively separated. Therefore, the reaction device is not suitable for catalytic substrates in seawater or sewage. The team of Academician Xie Heping of Shenzhen University demonstrated a reaction device for catalytic hydrogen production from seawater. Through a layer of hydrophobic membrane, the liquid environment can be isolated from the reaction site, and water vapor can pass through the hydrophobic membrane and enter the catalytic reaction site (Nature, 2022, 612, 673–678). The reaction device exhibits stable and efficient catalytic hydrogen production performance in seawater and greatly extends the service life of the catalyst. However, the generation and diffusion of this water vapor depends solely on the osmotic pressure between the liquid environment and the catalytic environment, thereby reducing the upper limit of the catalytic activity of the reaction device. Therefore, there is an urgent need for a highly integrated photocatalytic steam cracking reaction device that can efficiently and low-energy generate water vapor and carry out gas-solid two-phase photocatalytic hydrogen production activities nearby, while effectively isolating the contact between the liquid environment and the catalytic reaction site, and inhibiting the influence of adverse reaction environment on catalytic performance. Summary of the invention
[0005] In view of the defects of the prior art, the first object of the present invention is to provide a conical array aerogel, which couples a photothermal module and a photocatalytic module. Under illumination conditions, the photothermal module with a Wenzel-type superwetting surface and a vascular structure can generate sufficient water vapor to directly provide it to the photocatalytic module with high catalytic activity for photocatalytic hydrogen production, and the hydrophobic photothermal module can effectively isolate the photocatalytic module from the liquid environment without affecting the diffusion of water vapor; and through the special three-dimensional conical array design, not only can the photothermal module and the photocatalytic module play their roles at the same time, but the three-dimensional array structure can provide more illumination area, thereby greatly improving the catalytic hydrogen production efficiency; this three-dimensional spatial structure distribution allows the photothermal module and the photocatalytic module to form a reaction device in a highly integrated form, greatly reducing the difficulty and cost of preparing the photocatalytic water vapor cracking system.
[0006] The second object of the present invention is to provide a method for preparing a conical array aerogel, which is relatively simple, mature and streamlined, low-cost, and suitable for large-scale production.
[0007] The third object of the present invention is to provide a conical array aerogel for use as a photocatalytic reaction device in water splitting to produce hydrogen. The aerogel is suitable for splitting pure water, seawater or sewage to produce hydrogen, and the hydrogen production rate is fast and efficient. The conical array aerogel has good stability and is less affected by the environment, which is conducive to wide application.
[0008] In order to achieve the above technical objectives, the present invention provides a method for preparing a conical array aerogel, which comprises the following steps:
[0009] 1) electrospinning a spinning solution containing a titanium source and a spinning polymer to obtain spinning fibers, and annealing the spinning fibers to obtain titanium dioxide nanofibers;
[0010] 2) mixing titanium dioxide nanofibers with raw material I including water, hydrophilic polymer and coupling agent, filling the mixture into the conical cavity at the bottom of the conical array mold, and freezing the mixture; the bottom of the conical array mold is a plurality of regularly arranged conical cavities, and the top is a base cavity;
[0011] 3) Mixing raw material II including water, hydrophilic polymer, nano toughening agent, photothermal agent and coupling agent, filling into the base cavity at the top of the cone array mold, and freezing;
[0012] 4) After the liquid in the conical array mold is completely frozen, demoulding is performed, and then freeze-drying and solidification are performed to obtain the product.
[0013] The preparation process of the conical array aerogel catalytic material of the present invention first obtains titanium dioxide nanofibers with high photocatalytic activity through an electrospinning combined with an annealing process, and then uses titanium dioxide nanofibers and hydrophilic polymers to construct an aerogel photocatalytic module, and uses photothermal materials to construct an aerogel photothermal module. The photocatalytic module and the photothermal module are coupled through a special conical array mold to enhance the synergistic effect of the two in the photocatalytic water splitting hydrogen production process, thereby obtaining a conical array aerogel catalytic material with high catalytic hydrogen production efficiency.
[0014] As a preferred embodiment, the spinning solution comprises an alcohol solvent, a modulator, a titanium source and a spinning polymer; wherein the mass ratio of the alcohol solvent, the modulator, the titanium source and the spinning polymer is 8:(3-5):(3.5-5.5):(0.2-0.8). The alcohol solvent is mainly a low-carbon alcohol (C1-C5), such as methanol and ethanol. Common titanium sources include tetrabutyl titanate, isopropyl titanate, titanium trichloride, etc. The modulator is an acid compound that catalyzes the hydrolysis reaction of the titanium source and assists it in effective sol-solization, such as inorganic acids such as hydrochloric acid, and organic acids such as acetic acid and phytic acid. The spinning polymer is a polymer that is well known in the industry for electrospinning, such as polyvinyl pyrrolidone, polyethylene glycol, hyaluronic acid, chitosan, etc. The ratio of titanium source to spinning polymer should be strictly controlled within a range. If the titanium source is excessive relative to the spinning polymer, the resulting nanowire fibers will have poor toughness and be easy to break, making it difficult to form nanofiber materials of ideal length. If the spinning polymer is excessive relative to the titanium source, the photocatalytic activity of the resulting nanofibers will be low and cannot meet the design requirements.
[0015] As a preferred solution, the electrospinning conditions are as follows: voltage 10.0-20.0 kV, the distance between the collecting plate and the spinning needle is 10-25 cm, and the spinning solution feed rate is 0.5-3.5 mL min –1 Under the preferred spinning conditions, the diameter of the titanium dioxide nanofibers can be controlled to be about 100 nm.
[0016] As a preferred solution, the annealing conditions are: temperature of 300-600° C. and time of 1-3 hours. Under the preferred annealing conditions, anatase-type titanium dioxide with high photocatalytic activity is mainly obtained.
[0017] As a preferred solution, the mass ratio of water, hydrophilic polymer, titanium dioxide nanofiber and coupling agent in the raw material I is 100: (0.5-1.5): (0.5-2): (0.5-4). Hydrophilic polymer is the main material of aerogel, and the selection of hydrophilic polymer can improve the adsorption performance of aerogel to water vapor and improve the efficiency of photocatalytic hydrogen production. Common hydrophilic polymers include polyvinyl alcohol, polyethylene glycol, chitosan, polyacrylic acid, polyvinyl pyrrolidone, gelatin, etc. The coupling agent improves the stability and mechanical strength of aerogel materials through cross-linking. The coupling agent can be a silane coupling agent, such as KH-560. The mass ratio of hydrophilic polymer to titanium dioxide nanofiber is further preferably 1: 1-2 to obtain ideal photocatalytic activity, and the mass ratio of hydrophilic polymer to coupling agent is further preferably 1: 1-2 to meet the mechanical stability requirements of aerogel, and the mass ratio should not exceed 1: 4 to avoid affecting the photocatalytic activity of titanium dioxide nanofiber.
[0018] As a preferred solution, the number of conical cavities in the conical array mold is 36 to 100, the cone height of the conical cavity is 1000 to 7000 μm, the cone center distance is 500 to 4000 μm, the height of the base cavity is 3 to 8 mm, and the cross-sectional area of the base cavity is 4 to 16 cm 2 For example, the conical cavities in the conical array mold are arranged in 6 rows, with 6 cavities in each row, or in 10 rows, with 10 cavities in each row, and the design is carried out according to the needs.
[0019] As a preferred solution, the mass ratio of water, hydrophilic polymer, nano-toughening agent, photothermal agent and coupling agent in the raw material II is 100: (0.5-2): (0.5-2): (0.1-0.4): (1-4). The nano-toughening agent can improve the mechanical properties of the aerogel base, so that the aerogel can meet the catalytic use and provide sufficient mechanical support for the photocatalytic module. Common nano-toughening agents include nano-cellulose, nano-calcium carbonate, diatomaceous earth, halloysite, etc. The purpose of the photothermal agent is to convert light into heat, and heat the liquid surface to obtain vapor. At the same time, the heat can also be radiated to the photocatalytic module to enhance its photocatalytic performance. Common photothermal agents are carbon black, Prussian blue, carbon nanotubes, graphene, molybdenum disulfide, etc. In addition to improving the stability and mechanical strength of aerogel materials through cross-linking, coupling agents also provide sufficient hydrophobicity for aerogels. The purpose is to isolate the photocatalytic module from the liquid environment. Common coupling agents are silane coupling agents, such as vinyltrimethoxysilane, octadecyltrimethoxysilane, hexadecyltrimethoxysilane, etc.
[0020] As a preferred solution, the freeze-drying temperature is below -20°C and the time is 24 to 48 hours.
[0021] As a preferred solution, the cone array mold of the present invention is made of polydimethylsiloxane resin material.
[0022] As a preferred embodiment, the freezing treatment conditions of the present invention are: the temperature is in the range of -20°C to -80°C.
[0023] As a preferred solution, the curing treatment temperature is 90-110° C. and the time is 0.5-1.5 hours.
[0024] The present invention also provides a conical array aerogel, which is obtained by the preparation method. The conical array aerogel of the present invention is composed of a rectangular base and a conical array on the base; the conical array is a photocatalytic module, which has 36 to 100 conical aerogel photocatalytic units, and is constructed by a composite of hydrophilic polymers and titanium dioxide nanofibers, with a cone height of 1000 to 7000 μm and a cone center distance of 500 to 4000 μm. The conical array is distributed on the base, which is a photothermal module, with a base height of 3 to 8 mm and an upper surface area of 4 to 16 cm 2 The base is constructed of hydrophilic polymers and photothermal materials such as carbon black. The base is an aerogel with a Wenzel-type superwetting surface and vascular structure, and exhibits photothermal conversion performance.
[0025] The present invention also provides an application of a conical array aerogel catalytic material, which is used as a photocatalytic reaction device for water splitting to produce hydrogen, especially water splitting to produce hydrogen based on a gas-solid two-phase reaction.
[0026] The conical array aerogel of the present invention is placed in a reaction pool, which is filled with a certain amount of pure water, seawater or sewage and sealed with a quartz glass plate on the top. At the same time, high-purity nitrogen or argon is used as a carrier gas to carry the hydrogen generated by catalysis out of the reaction pool, and then two washing bottles are connected to remove impurities in the gas, such as methanol, a sacrificial agent for photocatalysis.
[0027] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0028] 1) The conical array aerogel of the present invention is coupled with a photocatalytic module and a photothermal module. The photocatalytic module and the photothermal module can absorb sunlight at the same time and play a synergistic role. The photothermal module has a Wenzel-type superwetting surface and a vascular structure, and has a photothermal conversion performance aerogel, which can increase the water vapor generation rate and provide water vapor for the photocatalytic module. At the same time, the photothermal module can transfer heat to the photocatalytic conical array by thermal diffusion and thermal radiation, and synergistically accelerate the gas product from the surface of the catalytic module to accelerate the photocatalytic hydrogen production reaction. The conical array aerogel has a three-dimensional conical array structure, leaving enough illumination area for the photothermal module to absorb sunlight and generate heat, and at the same time provides more area to the photocatalytic module compared to the two-dimensional plane, so that the photocatalytic module can also work normally. Due to this unique three-dimensional spatial structure distribution, the photothermal module and the photocatalytic module form a reaction device in a highly integrated form, which greatly reduces the preparation difficulty and manufacturing cost of the photocatalytic water vapor cracking system.
[0029] 2) The conical array aerogel of the present invention has strong liquid repellency by introducing hydrophobic silane compounds into the photothermal module, which can prevent the liquid environment from entering the photocatalytic module, thereby inhibiting the corrosion and erosion of the photocatalyst caused by viscous water, and reducing harmful side reactions caused by impure ions, so that the conical array aerogel is suitable for the hydrolysis and hydrogen production process of various wastewaters or seawater, and the photothermal module has a unique vascular structure, so that water vapor can quickly penetrate the base and enter the photocatalytic module.
[0030] 3) The photocatalytic module of the cone array aerogel of the present invention uses a hydrophilic polymer as the aerogel skeleton material, which is beneficial for the photocatalytic module to quickly adsorb water vapor and accelerate the photocatalytic reaction.
[0031] 4) The conical array aerogel of the present invention is used for water splitting to produce hydrogen. Based on the gas-solid two-phase photocatalytic reaction, the gas product (hydrogen) can be quickly detached from the catalyst surface, promoting the photocatalytic hydrogen production reaction from the reaction kinetics. At the same time, the photothermal module can transfer heat to the photocatalytic conical array by thermal diffusion and thermal radiation, and further synergistically accelerate the detachment of the gas product from the catalyst surface, thereby accelerating the photocatalytic hydrogen production reaction.
[0032] 5) The conical array aerogel of the present invention can be used in environments including seawater, heavy metal wastewater and organic dye wastewater, and can produce hydrogen at an extremely high rate.
[0033] 6) The preparation method of the conical array aerogel of the present invention is simple, the process is mature and streamlined, the cost is low, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0035] Figure 1 The preparation process and optical schematic diagram of the conical array aerogel device (the same below) in Example 1 of the present invention; a is the preparation process of the conical array aerogel device; b is an optical schematic diagram; c is a fluorescence confocal microscope photograph of the photothermal base after staining with sodium fluorescein, the fluorescence confocal microscope used is Olympus FV3000, and the scale is 100 μm; d is a SEM image of a unit in the conical array; c shows that the photothermal module aerogel has a vascular structure, which is conducive to the diffusion of steam and the absorption of light; d can be seen that titanium dioxide is evenly distributed on the conical array, and the conical array is tightly combined with the photothermal module.
[0036] Figure 2 Figure 1 is an optical schematic diagram and PXRD diagram of titanium dioxide nanofibers prepared by electrospinning in Example 1; a is an SEM image of carbon dioxide nanofibers; b is the PXRD spectrum of carbon dioxide nanofiber precursor and after annealing, and is compared with the anatase standard card; it can be seen from the figure that uniform and continuous titanium dioxide nanofibers are obtained by electrospinning, and the fibers after annealing show the crystallographic characteristics of anatase with high crystallinity.
[0037] Figure 3 This is an optical schematic diagram of the liquid repellency of the photothermal base of the conical array aerogel device prepared in Example 1. The solution was dyed with Rhodamine B in advance, and the bottom is an optical photograph taken under 365nm ultraviolet light. It can be seen from the figure that the obtained conical array aerogel device can float on the liquid surface, and during the fifteen-day placement process, the liquid did not enter the conical array with photocatalytic properties, which can effectively inhibit the corrosion and pollution problems caused by the liquid environment.
[0038] Figure 4 This is an optical schematic diagram of the hydrophilicity of the photocatalytic module of the conical array aerogel device prepared in Example 1; it can be seen from the figure that the photocatalytic module exhibits good hydrophilicity and can absorb droplets in a very short time. Figure 5 This is a thermal imaging image of the cone array aerogel device prepared in Example 1 under simulated sunlight. 0.2 represents photothermal module (as control), MN represents cone array aerogel device, PT / PCC 0.2Representing a two-dimensional photocatalytic module stacked on a photothermal module in a two-dimensional stacking manner (as a control), this group of pictures proves that the design of the three-dimensional conical array does not affect the function of the photothermal module. On the contrary, the two-dimensional plane stacking method will greatly reduce the performance of the photothermal module.
[0039] Figure 6 For Figure 5 Schematic diagram of three different devices.
[0040] Figure 7 This is an optical schematic diagram of the photocatalytic water vapor cracking hydrogen production line built in the laboratory. DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the examples of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0042] In the following embodiments, an electrospinning apparatus was built by itself with reference to the prior art, and it included a DC high voltage power supply, a microfluidic injection pump and a collection plate.
[0043] In the following examples, the freeze dryer model used is SCIENTZ-18N freeze dryer.
[0044] In the following examples, the polydimethylsiloxane resin mold used was customized and prepared by a secondary demolding method.
[0045] In the following examples, the chemical reagents used, unless otherwise specified, are conventional commercially available reagents.
[0046] The specific operation of the conical array device for hydrolysis and hydrogen production in the following specific embodiment is as follows: the conical aerogel device is placed in a reaction pool containing 20v / v% methanol / Yellow Sea water (or organic wastewater). The top of the reaction pool is covered with a quartz glass plate, and the entire reaction pool is sealed by snap-locking. The reaction pool is placed outdoors in a sunny place or under a xenon lamp simulated light source for photocatalytic activity. In order to collect the reaction gas products, compressed nitrogen or argon with a flow control device is used as a carrier gas at a rate of 5-50mL min –1 The reaction pool is purged at a flow rate of, and the tail gas passes through two scrubbers (containing water as scrubbing liquid) and finally enters the gas collection device.
[0047] Example 1
[0048] Add 4 g of acetic acid and 0.5 g of polyvinyl pyrrolidone to 1.8 g of ethanol, stir to dissolve, then add 4.5 g of tetrabutyl titanate under ice water and stir magnetically for 30 min.
[0049] 2. The obtained spinning solution was poured into a syringe and loaded into a homemade electrospinning device. The electrospinning voltage was 15.0 kV, the distance between the collecting plate and the spinning needle was 15 cm, and the spinning microfluidic pump rate was set to 1.5 mL min –1 .
[0050] 3. The collected titanium dioxide precursor was sent into a muffle furnace, calcined at 400°C for 2 hours in an air atmosphere, and then naturally cooled to room temperature.
[0051] 4. Take 100 mg of titanium dioxide nanofibers and add them to 10 g of a solution containing 100 mg of gelatin. Ultrasonic dispersion was performed for 30 min. After magnetic stirring for 1 h, 100 mg of KH-560 was added dropwise. After stirring for 4 h, the mixture was poured into a mold to fill the needle tip, and then frozen in a -20 °C refrigerator for 2 h.
[0052] 5. Take 10 g of dispersion containing 100 mg of nanocellulose, add 100 mg of polyvinyl alcohol, heat at 95°C until the polyvinyl alcohol is completely dissolved, add 80 mg of carbon black, ultrasonically disperse for 30 minutes, magnetically stir for 1 hour, then add 400 mg of vinyltrimethoxysilane, stir for 4 hours, pour into a mold, and then freeze in a -20°C refrigerator for 12 hours.
[0053] 6. Remove the cone array device from the film to obtain a cone array with a cone height of 5100μm, a cone center distance of 2700μm, and a cone number of 8×8. The base height is 3mm and the base area is 2.5×2.5cm 2 .
[0054] 7. The cone array device was placed in a freeze dryer for freeze drying for 36 h, and then incubated in an oven at 100°C for 1 h to completely cross-link and solidify, thereby obtaining a cone array aerogel device.
[0055] The prepared conical array aerogel device can convert a 20v / v% methanol / Yellow Sea water mixture into 8.8kg / m –2 h –1 The rate of evaporation was 127 mmol g cat –2 h –1 The device was exposed to light at room temperature for three months and still maintained more than 95% of its original performance. –1 Ionic solution (Fe 3+ , Cu 2+,I – 、NO3 – etc.) or 200 μg mL –1 It can maintain more than 95% of its original performance in organic dye wastewater (methylene blue, methyl orange, etc.).
[0056] Example 2
[0057] Add 4 g of acetic acid and 0.5 g of polyethylene glycol to 1.8 g of ethanol, stir to dissolve, then add 3.5 g of tetrabutyl titanate under ice water and stir magnetically for 30 min.
[0058] 2. The obtained spinning solution was poured into a syringe and loaded into a homemade electrospinning device. The electrospinning voltage was 15.0 kV, the distance between the collecting plate and the spinning needle was 15 cm, and the spinning microfluidic pump rate was set to 2.5 mL min –1 .
[0059] 3. The collected titanium dioxide precursor was sent into a muffle furnace, calcined at 450°C for 2 hours in an air atmosphere, and then naturally cooled to room temperature.
[0060] 4. Take 50 mg of titanium dioxide nanofibers and add them to 10 g of a solution containing 50 mg of chitosan. Ultrasonic dispersion was performed for 30 min. After magnetic stirring for 1 h, 100 mg of KH-560 was added dropwise. After stirring for 4 h, the mixture was poured into a mold to fill the needle tip, and then frozen in a -20 °C refrigerator for 2 h.
[0061] 5. Take 10 g of dispersion containing 100 mg of nano-diatomaceous earth, add 100 mg of polyvinyl alcohol, heat at 95 ° C until the polyvinyl alcohol is completely dissolved, add 80 mg of Prussian blue, ultrasonically disperse for 30 minutes, magnetically stir for 1 hour, then add 200 mg of hexadecyltrimethoxysilane, stir for 4 hours, pour into a mold, and then freeze in a -20 ° C refrigerator for 12 hours.
[0062] 6. Remove the cone array device from the film to obtain a cone array with a cone height of 5100μm, a cone center distance of 2700μm, and a cone number of 8×8. The base height is 3mm and the base area is 2.5×2.5cm 2 .
[0063] 7. The cone array device was placed in a freeze dryer for freeze drying for 36 h, and then incubated in an oven at 100°C for 1 h to completely cross-link and solidify, thereby obtaining a cone array aerogel device.
[0064] The prepared conical array aerogel device can convert a 20v / v% methanol / Yellow Sea water mixture into 9.5kg / m –2 h –1 The rate of evaporation was 147 mmol gcat –2 h –1 The device was exposed to light at room temperature for three months and still maintained more than 95% of its original performance. –1 Ionic solution (Fe 3+ , Cu 2+ ,I – 、NO3 – etc.) or 200 μg mL –1 It can maintain more than 95% of its original performance in organic dye wastewater (methylene blue, methyl orange, etc.).
[0065] Example 3
[0066] Add 4 g of acetic acid and 0.5 g of chitosan to 1.8 g of ethanol, stir to dissolve, then add 2 g of tetrabutyl titanate under ice water and stir magnetically for 30 min.
[0067] 2. The obtained spinning solution was poured into a syringe and loaded into a homemade electrospinning device. The electrospinning voltage was 20.0 kV, the distance between the collecting plate and the spinning needle was 15 cm, and the spinning microfluidic pump rate was set to 2 mL min –1 .
[0068] 3. The collected titanium dioxide precursor was sent into a muffle furnace, calcined at 350°C for 2 hours in an air atmosphere, and then naturally cooled to room temperature.
[0069] 4. Take 100 mg of titanium dioxide nanofibers and add them to 10 g of a solution containing 100 mg of polyacrylic acid. Ultrasonic dispersion was performed for 30 min. After magnetic stirring for 1 h, 200 mg of KH-560 was added dropwise. After stirring for 4 h, the mixture was poured into a mold to fill the needle tip, and then frozen in a -20 °C refrigerator for 2 h.
[0070] 5. Take 10 g of dispersion containing 100 mg of carboxymethyl cellulose, add 100 mg of polyacrylic acid, stir until the polyacrylic acid is completely dissolved, add 80 mg of carbon nanotubes, ultrasonically disperse for 30 minutes, magnetically stir for 1 hour, then add 200 mg of octadecyltrimethoxysilane, stir for 4 hours, pour into a mold, and then freeze in a -20°C refrigerator for 12 hours.
[0071] 6. Remove the cone array device from the film to obtain a cone array with a cone height of 5100μm, a cone center distance of 2700μm, and a cone number of 8×8. The base height is 3mm and the base area is 2.5×2.5cm 2 .
[0072] 7. The cone array device was placed in a freeze dryer for freeze drying for 36 h, and then incubated in an oven at 100°C for 1 h to completely cross-link and solidify, thereby obtaining a cone array aerogel device.
[0073] The prepared conical array aerogel device can convert a 20v / v% methanol / Yellow Sea water mixture into 8.2kg / m –2 h –1 The rate of evaporation was 139 mmol g cat –2 h –1 The device was exposed to light at room temperature for three months and still maintained more than 95% of its original performance. –1 Ionic solution (Fe 3+ , Cu 2+ ,I – 、NO3 – etc.) or 200 μg mL –1 It can maintain more than 95% of its original performance in organic dye wastewater (methylene blue, methyl orange, etc.).
[0074] Example 4
[0075] Add 4 g of acetic acid and 1 g of chitosan to 1.8 g of ethanol, stir to dissolve, then add 6 g of tetrabutyl titanate under ice water and stir magnetically for 30 min.
[0076] 2. The obtained spinning solution was poured into a syringe and loaded into a homemade electrospinning device. The electrospinning voltage was 15.0 kV, the distance between the collecting plate and the spinning needle was 15 cm, and the spinning microfluidic pump rate was set to 2 mL min –1 .
[0077] 3. The collected titanium dioxide precursor was sent into a muffle furnace, calcined at 350°C for 2 hours in an air atmosphere, and then naturally cooled to room temperature.
[0078] 4. Take 100 mg of titanium dioxide nanofibers and add them to 10 g of a solution containing 100 mg of polyvinyl alcohol. Ultrasonic dispersion was performed for 30 min. After magnetic stirring for 1 h, 100 mg of KH-560 was added dropwise. After stirring for 4 h, the mixture was poured into a mold to fill the needle tip, and then frozen in a -20 °C refrigerator for 2 h.
[0079] 5. Take 10 g of dispersion containing 100 mg of nano-montmorillonite, add 100 mg of sodium alginate, heat and stir at 60 ° C until the sodium alginate is completely dissolved, add 80 mg of graphene, ultrasonically disperse for 30 minutes, magnetically stir for 1 hour, then add 400 mg of vinyltrimethoxysilane, stir for 4 hours, pour into a mold, and then freeze in a -20 ° C refrigerator for 12 hours.
[0080] 6. Remove the cone array device from the film to obtain a cone array with a cone height of 5100μm, a cone center distance of 2700μm, and a cone number of 8×8. The base height is 3mm and the base area is 2.5×2.5cm 2 .
[0081] 7. The cone array device was placed in a freeze dryer for freeze drying for 36 h, and then incubated in an oven at 100°C for 1 h to completely cross-link and solidify, thereby obtaining a cone array aerogel device.
[0082] The prepared conical array aerogel catalytic device can convert 20v / v% methanol / Yellow Sea water mixture into 8.1kg / m –2 h –1 The rate of evaporation was 122 mmol g cat –2 h –1 The device was exposed to light at room temperature for three months and still maintained more than 95% of its original performance. –1 Ionic solution (Fe 3+ , Cu 2+ ,I – 、NO3 – etc.) or 200 μg mL –1 It can maintain more than 95% of its original performance in organic dye wastewater (methylene blue, methyl orange, etc.).
Claims
1. A method for preparing a conical array aerogel, characterized in that: The following steps are involved: 1) electrospinning a spinning solution containing a titanium source and a spinning polymer to obtain spinning fibers, and annealing the spinning fibers to obtain titanium dioxide nanofibers; 2) mixing titanium dioxide nanofibers with raw material I including water, hydrophilic polymer and coupling agent, filling the mixture into the conical cavity at the bottom of the conical array mold, and freezing the mixture; the bottom of the conical array mold is a plurality of regularly arranged conical cavities, and the top is a base cavity; 3) Mixing raw material II including water, hydrophilic polymer, nano toughening agent, photothermal agent and coupling agent, filling into the base cavity at the top of the cone array mold, and freezing; 4) After the liquid in the conical array mold is completely frozen, demoulding is performed, and then freeze-drying and solidification are performed to obtain the product.
2. The method for preparing a conical array aerogel according to claim 1, characterized in that: The spinning solution comprises an alcohol solvent, a modulator, a titanium source and a spinning polymer; wherein the mass ratio of the alcohol solvent, the modulator, the titanium source and the spinning polymer is 8:(3-5):(3.5-5.5):(0.2-0.8).
3. The method for preparing a conical array aerogel according to claim 1 or 2, characterized in that: The electrospinning conditions are as follows: voltage of 10.0-20.0 kV, distance between the collecting plate and the spinning needle of 10-25 cm, feeding rate of the spinning solution of 0.5-3.5 mL / min –1 .
4. The method for preparing a conical array aerogel according to claim 1, characterized in that: The annealing conditions are: temperature of 300-600° C. and time of 1-3 hours.
5. The method for preparing a conical array aerogel according to claim 1, characterized in that: The mass ratio of water, hydrophilic polymer, titanium dioxide nanofiber and coupling agent in the raw material I is 100:(0.5-1.5):(0.5-2):(0.5-4).
6. The method for preparing a conical array aerogel according to claim 1, characterized in that: The number of conical cavities in the conical array mold is 36 to 100, the cone height of the conical cavity is 1000 to 7000 μm, the cone center distance is 500 to 4000 μm, the height of the base cavity is 3 to 8 mm, and the cross-sectional area of the base cavity is 4 to 16 cm 2 .
7. The method for preparing a conical array aerogel according to claim 1, characterized in that: The mass ratio of water, hydrophilic polymer, nano toughening agent, photothermal agent and coupling agent in the raw material II is 100:(0.5-2):(0.5-2):(0.1-0.4):(1-4).
8. The method for preparing a conical array aerogel according to claim 1, characterized in that: The freeze drying temperature is below -20°C and the time is 24 to 48 hours; The curing treatment is performed at a temperature of 90 to 110° C. and for a time of 0.5 to 1.5 hours.
9. A conical array aerogel, characterized in that: The method is obtained by any one of claims 1 to 8.
10. The use of a conical array aerogel according to claim 9, characterized in that: It is used as a photocatalytic reaction device to produce hydrogen by splitting water.
Citation Information
Patent Citations
Cellulose nanofiber aerogel photo-thermal interface water evaporation material and preparation method thereof
CN114405421A
Preparation method of asymmetric wettability polyimide fiber-based photo-thermal aerogel
CN115651265A